(3GdeOQSI hGdCgd(B: (3ef GdeUdMI GdeTJQcI Edi GdTQGcI aj GdJQHjIs - (3aVhd, Sjehfs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2006)
(3ddYdGbI Hjf GdeOQSI hGdCgd JGQjN Whjd HOC eY HOGjI eSjQI GdJYqde(B. (3hbO OQLJ GdYGOI Cf jgqJe GdCgd HGdJQHjI djJaqQZ GdeYqdehf (B((3GdeOQSI(B) (3ddJYdje(B. (3hbO GYJGO GdcKjQhf Ydi acQmI eG HQM HYV GdeOqQSjf eJYqdbjf HgG EP jQqOOhf(B: "(3adjQpqH GdCgd ChdGOge hdjOYhG GdJYdje dfG(B". (3ZjQ Cqf gPG GdhGbY HOC jJZqjQ aj GdSfhGJ GdCNjQI eY JfGej GgJeGe GdCgd HJMUjd ChdGOge GdYdej, hHMjGJge aj GdeOQSI GjVkG heOi JaGYdge hfhYjI GdJQHjI GqdJj jJdqbhfgG(B. (3cPdc HOC GdHYO GdJQHhoqj jToqb WQjbg aj Uaha YOO cHjQ ef GdeQqHjf, EOGQjjf heYqdejf eDefjf Cqf Yedge eY GdChdGO gh Yed TGed jWGd feqhge GdeJcGed; aceG Ydjge JhajQ CaVd aQU GdJYqde GdCcGOjej ddhdO, cPdc Ydjge Cf jhGcHhG feqhg GdNdbj hGdfaSj hGdLSOj hUhdkG Ydi GdgOa GdCSei hgh HfGA EfSGf eJcGed LGgR dehGLgI JMqOjGJ GdMjGI Ydi GNJdGagG(B. (3hbO Bf GdChGf Cf jYj YGdefG GdYQHqj gPg GdMbjbI ajfcqH Ydi UhZ TNUqjI GdhdO hJfejJgG ef NdGd QHW GdJYqde HGdJQHjI HTcd Yejb HMjK jUHM Gdbqjehf GdeHGTQhf Ydi JQHjI GdhdO, Cj GdHjJ hGdeOQSI, TQcGA aYdqjjf aj GdYedjI GdJQHhqjI(B. (3ef gPG GdefXGQ, dG fSJWjY Cf ffXQ Ydi GdeOQSI hGdHjJ chMOJjf efaUdJjf YfOeG jJYqdb GdCeQ HJQHjI GdChdGO hfeqhge(B. (3EfeG YdjfG Cf fJCqed hHYeb, HGdTQGcI GdJj jLH bjGegG hJYRjRgG HjfgeG aj bdH GdeLJeY(B. (3hJbhe gPg GdTQGcI Ydi aQVqjGJ NeS CSGSjI(B: 1. (3GdCgd jQjOhf GdCaVd dChdGOge (B2. (3HZqV GdfXQ Yf eOi KbGaJge hhVYge GdGLJeGYj, jHbi GdCgd eUOQkG CSGSjkG dJfejI ChdGOge(B. 3. (3GdeOQSI JQjO Gf JQi JdGePJgG jMqbbhf GdfLGM Ydi eNJda GdoUoYO EP Eqf fLGMge gh fLGM dgG(B. 4. (3cqd GdChdGO jecf Cf jJYqdehG, jHbi Cf jLO GdeQqHhf eY GdCgd GdEjbGY GddGRe hGdeaGJjM GdVQhQjI deSGYOI cd hGMO Ydi GdfLGM(B. 5. (3eYkG, CgdkG heOQSI heLJeYkG jSJWjYhf Cf jQqHhG CLjGdkG aGYdI efJLI JHfj GdeLJeY hGdhWf(B. (3jgOa gPG GdcJqjH Edi GdJhqba YfO CgeqjI GdYdGbI GdEjLGHjI Hjf GdeOQSI hGdCgd hcjaqjI bjGegG hQYGjJgG dJDJj GdKeGQ GdeQLqhI hdJfJbd ef YdGbI GdeUdMI Edi YdGbI GdTQGcI, hjJVqef ebOeI hSHYI aUhd hNGJeI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Etablissement scolaire et parents; School and Parents; (3GdeOQSI hGdCgds